A biogeographical approach to characterizing the climatic, physical and geomorphic niche of the most widely distributed mangrove species, Avicennia marina. (20th October 2022) - Martínez‐Díaz, Marycarmen G.; Reef, Ruth
Abstract: Aim: Mangroves are coastal ecosystems exposed to terrestrial, marine, geomorphic and climatic forcings operating in concert, making the mangrove niche hard to define, as evidenced by extremely poor restoration outcomes. We have developed a set of high‐resolution species distribution models and interpreted the variables that have the largest impact on the niche of Avicennia marina, the most globally widespread mangrove species, to comprehensively detail the forcings driving habitat suitability. Location: Australia. Time period: 1970–2020. Major taxa studied: Avicennia marina (Forssk.) Vierh. Methods: We modelled the suitable habitat for A . marina in Australia using the maxent method incorporating 38 environmental variables and the Global Mangrove Watch baseline for the presence records. Using k‐means grouping, we identified subregions where similar suites of environmental variables influence habitat suitability, while also identifying biogeographical commonalities among the subregions. To better understand the low realization of the fundamental niche, we analysed the other land covers occupying the niche. Results: Avicennia marina in Australia occupies six different environmental subregions. Maxent distribution models accurately predicted the presence of A . marina in each subpopulation (AUC > 0.9). A . marina 's presence in all subregions was strongly determined by its proximity to freshwater. Precipitation and temperature extreme values were more important than average values in predicting the species presence. The species requires low‐energy coastlines with high solar radiation. The suitable areas are primarily shared with salt marshes, seagrass and buildings or cleared land. Main conclusions: Our results offer a baseline for the suitable area of A . marina 's presence that includes a range of environmental conditions, A . marina currently occupies <50% of its suitable habitat, and there is scope for restoration with significant ecosystem service gains. The six different subregions in Australia map to known phylogenetically distinct populations, indicating genetic plasticity in response to region specific climatic conditions.